2022
DOI: 10.1088/1758-5090/ac5fb7
|View full text |Cite
|
Sign up to set email alerts
|

3D bioprinted, vascularized neuroblastoma tumor environment in fluidic chip devices for precision medicine drug testing

Abstract: Neuroblastoma is an extracranial solid tumor which develops in early childhood and still has a poor prognosis. One strategy to increase cure rates is the identification of patient-specific drug responses in tissue models that mimic the interaction between patient cancer cells and tumor environment. We therefore developed a perfused and micro-vascularized tumor-environment model that is directly bioprinted into custom-manufactured fluidic chips. A gelatin-methacrylate/fibrin-based matrix containing multiple cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 53 publications
0
49
0
Order By: Relevance
“…Different strategies have been developed to this end. In many cases, fugitive inks were used that produced a distinct vascular pattern during the printing process and were removed post-printing during the culture period [ 37 , 38 ]. Compared to widely used extrusion-based bioprinting, DLP combines the advantages of extraordinarily high resolution and high stability of the produced constructs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different strategies have been developed to this end. In many cases, fugitive inks were used that produced a distinct vascular pattern during the printing process and were removed post-printing during the culture period [ 37 , 38 ]. Compared to widely used extrusion-based bioprinting, DLP combines the advantages of extraordinarily high resolution and high stability of the produced constructs.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the physiological relevance of the model further, the channel needs to be seeded with endothelial cells, e.g., HUVECs, in further optimization experiments. Previous studies have shown that a tight endothelial lining can be achieved by post-printing seeding of cells and slow rotation of the model to ensure even distribution of the cells on the entire vessel wall [ 38 ]. The tight endothelium will hinder substances from easily penetrating into the model and thereby more realistically simulate the pharmacokinetic features of human patients.…”
Section: Discussionmentioning
confidence: 99%
“…Functional short-time cultures of both tumor cells and immune cells in a microfluidic system have been reported for adult cancers ( 125 , 126 ) and might be applicable also to pediatric cancers. Very recently, the first bioprinted, vascularized NB microenvironment on a fluidic chip was reported ( 127 ). Implantation of cell line-derived NB spheroids led to NB cell survival for two weeks and successful micro-vessel infiltration of the spheroids ( 127 ).…”
Section: Current and Future Model Optimizationmentioning
confidence: 99%
“…Very recently, the first bioprinted, vascularized NB microenvironment on a fluidic chip was reported ( 127 ). Implantation of cell line-derived NB spheroids led to NB cell survival for two weeks and successful micro-vessel infiltration of the spheroids ( 127 ). A different study managed to establish PD NB organotypic slice cultures that could potentially preserve an intact NB tumor microenvironment ( 88 ).…”
Section: Current and Future Model Optimizationmentioning
confidence: 99%
“…These models require the reconstitution of the complexity and heterogeneity of glioblastoma and neuroblastoma tissues, and additionally, the special tumour-stroma interactions and blood-brain barriers for accelerating potential therapeutic interventions ( 84 ). These models represent scaffold-free 3D bioprinted spheroid cultures or co-printed, co-cultured glioblastoma or other CNS malignancy-derived tumour cells (e.g., neuroblastoma) cells with the associated macrophages, stromal cells to build the special microenvironment ( 85 , 86 , 87 , 88 ). To develop more reliable models in these diseases, patient-derived newly isolated glioma cells are preferred instead of traditional glioma cell lines which were long cultured in 2D cultures ( 89 ), and another research direction is to combine these with 3D bioprinted blood-brain barrier models ( 90 , 91 ).…”
Section: Introductionmentioning
confidence: 99%